The Effects on consumers of using refills under Law No. 8 of 1999 on Consumer Protection - Dedi Kiswanto; Herlina Hanum Harahap (Inovasi Pratama Internasional. Ltd, 2024)
The purpose of this research is to determine and analyze the legal protection of the impact of using refill perfume on consumers based on Law Number 8 of 1999 concerning Consumer Protection, obstacles to the impact of using refill perfume on consumers based on Law Number 8 of 1999 concerning Consumer Protection and solutions to the impact of using refill perfume on consumers based on law number 8 of 1999 concerning consumer protection. This research is The field research method, which involves conducting research in an actual field setting, is a common methodology employed in legal research. Prior to conducting any research project, the researcher should determine the most appropriate method for the study at hand. The results of the research are the continued disadvantage of consumer rights by business actors in terms of refill perfume. The responsibility of business actors for losses suffered by consumers who use cosmetic products, in this case refill perfumes, is contingent upon the clarity of the product label. The responsibility of business actors is also referenced in Article 1365 of the Civil Code concerning Consumer Protection, consumers who have been harmed as a result of using dangerous refillable perfume oil may pursue legal remedies through out-of-court dispute resolution.